Selection and valuation of criteria in decision-making for improvements in transport systems - Bertelsen, Dag (Proceedings from the Annual Transport Conference at Aalborg University, 2008)
The aim of all decision-making, for companies as well as for the society as a whole, is to choose the best among a number of alternative solutions. However, what is “the best” will often depend on a judgement of the importance of different aspect of the alternatives. Variation in judgement among the decision-makers will lead to different conclusions as to which solution is the best. Variation in assessment of relevant aspects is a natural and sound ingredient in decision-making. On the other hand, lack of consistency and completeness in the set of aspects included in the decision basis will normally lead to questionable decisions. Unconsciousness in the assessment of different aspects and solutions may also result in illogical decisions. This paper will focus on these two essential points in decision processes in order to increase rationality in decision-making. This paper addresses the following issues: Single-criteria decision-making Multi-criteria decision-making Cause-effect models in decision support Consistent sets of decision-criteria Valuation of criteria in a multi-criteria decision Political and professional duties in the decision-making process A procedure to obtain better decisions